Catalysing interdisciplinary research at Massey University - Goodyer JE; Ryan A; Robertson T (Massey University, 2017)
As the research environment in which Massey University operates shifts to prioritise high-impact research and interdisciplinary research, it is imperative that the University acts proactively to develop the necessary capability to respond to these changes. From the findings of this research we propose that a key mechanism for helping to catalyse interdisciplinary research at Massey can be provided through establishing an ‘Integration and Implementation Sciences framework’ at Massey. An Integration and Implementation Sciences framework has immediate resonance in relation to wicked problems associated with fields such as Agrifood, sustainability and health. Interdisciplinary research is to be encouraged and supported through the creation of a new centrally-funded IDR seed fund. A key mechanism to support the development of staff expert in interdisciplinary research is through the creation of a ‘Framework for Interdisciplinary Research Professional Development’